A proposta de iniciação à docência na formação inicial de professores: uma análise do PIBID no contexto do curso de Pedagogia/UFMA - LIMA, Andréia Carolina Severo (2017)
The research presented in this dissertation approaches the theme of teacher training based on the proposal of initiation to teaching of PIBID in the context of the Pedagogy / UFMA course. Motivated by the understanding that teacher education stands out as a condition for facing the various problems that affect Basic Education, our central objective sought to analyze the initial formation of the students of the Pedagogy course of the Federal University of Maranhão while scholarship holders of PIBID, revealing the contribution of the proposal of this Program to the initial formation of teachers for Basic Education. PIBID is now one of the main programs for the promotion and promotion of teaching, and in the context of UFMA it is the Program with the largest number of grants awarded. In order to do so, this study had the theoretical contribution of Freitas (2002), Nóvoa (2009), Romanelle (2010), Shiroma et al (2011), Nono (2011), Imbérnon (2010), Gati; Barreto (2009), which, among others, provided great contributions. Thus, this research was based on a qualitative approach with the development of bibliographical studies of available literature and documentary analysis. As an instrument to obtain the empirical data, we used semi-structured interviews, and after being transcribed were treated from the content analysis. A total of eight subjects participated in this study, of which five were PIBID / Pedagogy Scholars, the Institutional Coordinator, the Area Former Coordinator and a Public School Supervisor Professor, who were willing to collaborate to carry out this study. Among the results, our research demonstrated that the Program in the context of the Subproject of Pedagogy / UFMA has been constituted as a space of construction of a new knowledge, produced in the relations between institutions and subjects, integrating the different knowledge that constitute professional knowledge. We also show the exchange between university/school, as well as a reasonable relationship between theory and practice, thus meeting the objectives of the Program. Some limits were also evidenced, for example: lack of resources for the development of activities; the limited number of fellowships for teaching initiation, and partly the performance of some of the supervising teachers of the partner schools, while exempting themselves from the role of coformers as the Program suggests.